2014
DOI: 10.3109/13880209.2014.912240
|View full text |Cite
|
Sign up to set email alerts
|

Withania somniferashows a protective effect in monocrotaline-induced pulmonary hypertension

Abstract: Context: Withania somnifera (Linn.) Dunal (Solanaceae), a clinically used herbal drug in Ayurveda, shows potent antioxidant, anti-inflammatory, pro-apoptotic, and cardioprotective effects. However, the efficacy of W. somnifera in pulmonary hypertension (PH), a cardiopulmonary disorder, remains unexplored. Objective: The present study investigates the effect of W. somnifera root powder on monocrotaline (MCT)-induced PH in rats. Materials and methods: In preventive studies, W. somnifera root powder (50 and 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…The major constituent in Ashwaganda, identified as Withaferin A, itself is an inhibitor of HMG-CoA, angiotensinogen-converting enzyme, (Ravindran et al, 2015b) can lower total cholesterol, triglycerides, higher HDL/LDL ratios (Shukla et al, 2014) and reduce severity or incidence of myocardial infarction, (Khalil et al, 2015) stroke (Ahmad et al, 2015, Raghavan and Shah, 2015, Sood et al, 2015) and hypertension. (Kaur et al, 2015) As far as glial cells, little has been investigated, but it has been reported that Withaferin A has potential in treatment of glioblastoma multiforme (Chang et al, 2016) with possible future therapies to target brain tumors (Kataria et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The major constituent in Ashwaganda, identified as Withaferin A, itself is an inhibitor of HMG-CoA, angiotensinogen-converting enzyme, (Ravindran et al, 2015b) can lower total cholesterol, triglycerides, higher HDL/LDL ratios (Shukla et al, 2014) and reduce severity or incidence of myocardial infarction, (Khalil et al, 2015) stroke (Ahmad et al, 2015, Raghavan and Shah, 2015, Sood et al, 2015) and hypertension. (Kaur et al, 2015) As far as glial cells, little has been investigated, but it has been reported that Withaferin A has potential in treatment of glioblastoma multiforme (Chang et al, 2016) with possible future therapies to target brain tumors (Kataria et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary vascular remodelling, which includes thickening of pulmonary vasculature, plays an important role in PH (Kaur et al , ). Histopathological studies of lungs of MCT‐treated rats showed pulmonary vascular remodelling in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Following the measurement of the RVP, animals were killed; the wall of the RV, left ventricular (LV) wall and ventricular septum (S) were separated from the rats’ hearts. The Fulton index (RV/LV + S), a marker of hypertrophy, was determined (Kaur et al , 2015a,b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its primary bioactive compound (Withaferin A) directly inhibits β1-adrenergic receptors, HMG-CoA, angiotensinogen-converting enzyme, total cholesterol, triglycerides, low density lipoprotein and elevation of protective high density lipoproteins and endogenous antioxidant systems [86, 87]. In animal models, WS prevents isoproterenol induced myocardial infarction, stroke distal middle cerebral artery occlusion and monocrotaline induced pulmonary hypertension in rats [8891]. With respect to the immune system, WS can attenuate mitogen induced T/B-cell activation, secretion of Th1 and Th2 cytokines and inhibit NF-κB nuclear translocation in lymphocytes [92].…”
Section: Discussionmentioning
confidence: 99%